2004
DOI: 10.1016/s0002-9440(10)63243-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Function of Trefoil Factor Family 3 Expression in the Biliary Tree

Abstract: Microarray analysis identified trefoil factor family 3 (TFF3) as a gene expressed in biliary epithelial cells (BECs), regulated by interleukin (IL)-6, and potentially involved in biliary pathophysiology. We therefore studied the regulation and function of BEC TFF3, in vitro and in vivo in IL-6 ؉/؉ and IL-6 ؊/؊ mice subjected to chronic bile duct ligation for 12 weeks. In vitro studies showed that IL-6 wild-type (IL-6 ؉/؉ ) BECs expressed higher TFF3 mRNA and protein levels than IL-6-deficient (IL-6 ؊/؊ ) BECs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 46 publications
4
27
0
Order By: Relevance
“…40 In the biliary tract, IL-6 knockout mice were sensitive to biliary cirrhosis after bile duct ligation. 41,42 Consistent with the role of GP130/STAT3 in tissue repair, the present study demonstrated that the activation of STAT3 in airway epithelial cells following naphthalene injury was blocked in Gp130 ⌬/⌬ mice. The observation that abnormalities in bronchiolar repair were similar in Stat3 ⌬/⌬ and Gp130…”
Section: The Role Of Gp130-stat3 Signaling In Wound Repairsupporting
confidence: 84%
“…40 In the biliary tract, IL-6 knockout mice were sensitive to biliary cirrhosis after bile duct ligation. 41,42 Consistent with the role of GP130/STAT3 in tissue repair, the present study demonstrated that the activation of STAT3 in airway epithelial cells following naphthalene injury was blocked in Gp130 ⌬/⌬ mice. The observation that abnormalities in bronchiolar repair were similar in Stat3 ⌬/⌬ and Gp130…”
Section: The Role Of Gp130-stat3 Signaling In Wound Repairsupporting
confidence: 84%
“…25 Screening gene array analysis suggested that noncoordinate upregulation of the BEC SPRR2 genes might be at least partially responsible for the phenotype observed in the IL-6 À/À mice. 26 SPRR expression has not been previously described in the liver. Therefore, this initial study was carried out to investigate the (patho-)physiologic function(-s) of SPRR2 in the biliary tree.…”
mentioning
confidence: 86%
“…It is also expressed in pancreatic b cells and oxytocin-secreting neurons in the hypothalamus, related to cell growth and learning and memory (Jagla et al, 2000;Fueger et al, 2008;Shi et al, 2012). This peptide is induced in biliary duct epithelial cells in biliary diseases (Srivatsa et al, 2002;Nozaki et al, 2004;Sasaki et al, 2007;Jiang et al, 2010). The TFF3 gene maps to the Obq4 obesity quantitative trait locus, which is highly associated with total calorie intake; indeed, the expression of Obq4 in the intestine is regulated by food intake (Kumar and Smith Richards, 2008;Ge et al, 2015).…”
Section: Crosstalk Of Nrf2 and Estrogen Signaling In Lipid Metabolismmentioning
confidence: 99%